Salt Weathering on Buildings and Stone Sculptures. - Pavia, Sara (My University, 2008)
This paper concentrates in the phenomenon of sulfate formation within an old cement paste dating from c.1878, leading to damage of the mortar and its adjacent masonry. Samples of mortar and salt efflorescence were taken for XRD, XRF, petrographic and SEM/EDAX analyses. SEM/EDAX revealed detail on the clinker microstructure and the presence and arrangement of sulfates including kieserite, syngenite and calcium langbeinite. Gypsum, thenardite, picromerite, aphthitalite, ettringite, niter and potassium calcium carbonate were detected by XRD analysis. Under the petrographic microscope, the mortars displayed strong damage by expansion with abundant, fractured, residual cement clinkers, extensive sulfate replacement, carbonation and alkali-agregate reaction. The paper concludes that damage is caused by sulfation (mainly by gypsum and thenardite). Sulfate damage is closely related to the location of the portland cement (PC) repair, suggesting that the sulfate source is internal, originating from a suphur-rich clinker phase in the cement. However, ground contamination is probably a further source for sulfate. Based on the nearly total absence of ettringite and other calcium sulfoaluminates and the abundance of alkali sulfates such as thenardite and aphthitalite, the paper suggests that the original cement clinker was low in aluminium and probably high in alkalis. Gypsum was the most common phase recorded in the solid mortars whereas thenardite was the most abundant phase in the efflorescence. This may be due to the lower solubility of gypsum when compared to that of thenardite. This paper also concludes that, despite the vaste amount of outstanding research on the reactions responsible for sulfate release from primary cement phases such as primary ettringite and C-S-H, the `time elapsed? is an important parameter that is often overlooked. For example, does decomposition of primary ettringite take place only at high temperatures (>70?C) or can this take place at ambient temperatures over long time periods i.e. 100 years?
SWBSS 1st Int. Conf. Salt Weathering of Buildings and Stone Sculptures
PUBLISHED
Denmark
Keywords: Alkali cement; high-sulfur clinker; gypsum; thenardite; picromerite; aphthitalite